Analysis of Sustainable Domestic Cooperation Administration for Enhancing Educational Management Effectiveness at Universitas Pembangunan Panca Budi - Rahayu, Sri; Desy Surya, Elfitra; Andriani Lubis, Dini (International Conference Epicentrum of Economic Global Framework, 2026)
This study examines the role of sustainable domestic cooperation administration in enhancing the effectiveness of educational management at Universitas Pembangunan Panca Budi. Sustainable cooperation administration is essential for strengthening institutional governance, improving collaboration with domestic stakeholders, and ensuring the continuity of academic, research, and community engagement activities. This research employed a quantitative approach using a survey method involving university leaders, faculty members, and administrative staff engaged in managing domestic cooperation programs. Data were collected through structured questionnaires and analyzed using descriptive statistics and multiple regression analysis. The findings indicate that sustainable domestic cooperation administration has a significant positive effect on educational management effectiveness. Effective administrative practices, including systematic planning, implementation, monitoring, documentation, and evaluation of cooperation agreements, contribute to improved institutional performance, decision-making, resource utilization, and stakeholder satisfaction. Furthermore, sustainable cooperation enhances organizational accountability and supports the achievement of strategic institutional goals. The study concludes that strengthening the administrative management of domestic partnerships is a strategic approach to improving educational management effectiveness in higher education institutions. The findings provide practical recommendations for university leaders to develop integrated cooperation management systems that promote sustainability, institutional quality, and long-term organizational performance.